(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of Indonesia’s macroeconomic and foreign transactions on the Composite Stock Price Index. The data analysis technique used in this study is to use linear regression analysis multiple. The data used in this study is the time series data for the 2016-2018 period. SBI variable has a negative and significant effect on composite. Inflation, Exchange Rate, SBI, Amount of Money Supply and net foreign transactions Simultaneously influence the composite. whereas partially the variables that influence the composite are the exchange rate, the SBI and the money supply. Macroeconomic variables used in this study can explain the composite of 61%, while the rest is influenced by other variables. Investors should decide before investing to take into account macroeconomic variables. The difference between this study and previous research adds the variable Number of Outstanding Shares and foreign transactions in the Indonesian capital market